2020
DOI: 10.7196/samj.2020.v110i11.15249
|View full text |Cite
|
Sign up to set email alerts
|

COVID deaths in South Africa: 99 days since South Africa’s first death

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 5 publications
1
35
0
Order By: Relevance
“…This drop in the number of natural deaths resulted in the development of the adjustment to the base to calculate the excess natural deaths. The 60 -69-year-olds were most affected at the peak of the surge, accounting for 28% of the excess natural deaths, the highest proportion of all 10-year age groups, and similar to the proportion of confirmed COVID-19 deaths in the first months of the pandemic (26%), [23] as well as deaths reported on the hospital surveillance system by the end of 2020 (27%). [24] It is possible that excess deaths due to COVID-19 occurred earlier in this age group than in other age groups, obscuring any drop in the number of deaths resulting from lockdown.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This drop in the number of natural deaths resulted in the development of the adjustment to the base to calculate the excess natural deaths. The 60 -69-year-olds were most affected at the peak of the surge, accounting for 28% of the excess natural deaths, the highest proportion of all 10-year age groups, and similar to the proportion of confirmed COVID-19 deaths in the first months of the pandemic (26%), [23] as well as deaths reported on the hospital surveillance system by the end of 2020 (27%). [24] It is possible that excess deaths due to COVID-19 occurred earlier in this age group than in other age groups, obscuring any drop in the number of deaths resulting from lockdown.…”
Section: Discussionmentioning
confidence: 85%
“…Government is urged to improve the cause-of-death information system going forward so that the current and long-term impact of the pandemic can be assessed more fully and information to prioritise responses can become available. [23] In particular, it is essential to ensure that the NDoH has access to cause-of-death information at the time of death registration to inform public health actions. [29] Declaration.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Recent US database studies found, in their population, higher COVID-19 mortality rates among people with psychiatric [11,12] or substance use disorders [13] compared with those without such disorders. As with the study by Pillay-van Wyk et al, [2] their findings are dependent on accurate death records. While such accuracy is lacking for most conditions in SA, it is particularly so for mental disorders.…”
mentioning
confidence: 76%
“…
Mental illness: South Africa's blind spotTo the Editor: The articles by Odendaal et al [1] and Pillay-van Wyk et al [2] indicate poor recognition of mental illness and its complex interplay with physical health in South African (SA) research. While Odendaal et al [1] screened for depression in pregnant women, the relationship between mental illness and persistent smoking was not explored and the possible need to tailor interventions to perceptual, cognitive or personality functioning was not discussed.
…”
mentioning
confidence: 99%
See 1 more Smart Citation